Intercostal Neurinoma: A Rare Cause of Persistent Thoracic Pain - Meyer, Christian; Rodepeter, Fiona; Bartsch, Detlef; Kirschbaum, Andreas (The Thoracic and Cardiovascular Surgeon Reports, 2014)
Persistent thoracic pain with no history of trauma demands diagnostic workup. In this case, the patient complained of right thoracic continuous belt-like pain, sometimes experienced as shooting pain, over several months. The symptoms were first treated conservatively with painkillers, which was rather ineffective. A magnetic resonance imaging scan of the thorax surprisingly showed an unclear piston-like enlargement near the seventh rib closely above the spinal canal. Video thoracoscopy was performed to provide further clarification. This showed two lesions of the intercostal nerves of the seventh and eighth ribs. The intercostal nerves were resected in these areas. Histological examination revealed two neurinomas of the intercostal nerves with focal outgrowth of a neural cyst measuring 1.6 cm on the seventh intercostal nerve. The patient was free of any pain after the operation.
Keywords: thoracic surgery; chest wall; thoracoscopy/VATS